Hoàn thiện quá trình đào tạo giáo viên tiểu học có trình độ Đại học ở các tỉnh Miền Trung - Phạm, Minh Hùng (Bộ Giáo dục và Đào tạo, 2013)
The article deals with the following problems : - Necessity for univers alizing primary school teachers in the middle provinces of Vietnam . - To train the body of the primary school teachers . we must take an integrated set of measures for various aspects : training objective .enrolling students teaching program, content and method. the body of teachers. material base and other teaching aids .. .